INTEGRASI ELECTRONIC MEDICAL RECORD (EMR) DENGAN LABORATORY INFORMATION SYSTEMS (LIS) DAN PICTURE ARCHIVING AND COMMUNICATIONS SYSTEM (PACS) - Antik Pujihastuti (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2018)
Currently, many hospitals in developed countries have considered laboratory information system (LIS) and PACS as needs, and are important sub-systems in EMR. While in some developing countries, this is a novelty and plans related to integration with EMR are still not the main subject, as many still assume that LIMS and PACS are systems separate from EMR. Types This article is a systematic review. The author uses the Literature Review Method approach. Integration of Electronic Medical Record (EMR) with LIS and PACS requires some preparation and several aspects to be considered, which include: 1) Requirements for data standards and medical terminology, (2) Aspects of privacy and data security, (3) Implementation of data entry , (4) Preparation and Requirement Analysis of Technology / Information System, (5) Leadership Policy and Support, (6) Standart and Protocol System, (7) Pattern and Model of System Integration, (8) Standardization of Protocol and Communication of OSI.